Inflamassomos NLRC4 E NLRP3 na Doença Periodontal Experimental Induzida por Aggregatibacter Actinomycetemcomitans - Rocha, Fernanda Regina Godoy [UNESP] (2016)
Inflammasomes are multi-protein complexes that can amplify the inflammatory signal in situations involving host-microbial interactions and host tissue destruction, such as chronic periodontal disease. There is a relative scarcity of information on the role of NLRC4 and NLRP3 inflammasomes in periodontal disease. In this study, we used a model of bacteria-initiated periodontal disease in WT, Ipaf-knockout (Ipaf-KO), Caspase 1-knockout (Casp1-KO) and NLRP3-knockout (NLRP3-KO) mice to describe the effect of those inflammasomes on inflammation and alveolar bone resorption. Heat-killed Aggregatibacter actinomycetemcomitans (Aa) were injected in the gingival tissues on the palatal aspect adjacent to first molars of wild-type (WT), Ipaf-KO, Casp1-KO and NLRP3-KO mice, and control animals received the suspension vehicle (PBS). Severity of bone resorption was quantitated by μCT analysis. Inflammation was assessed by immunofluorescence, verifying the presence and intensity of a pan-leukocyte (CD45) and a neutrophil (Ly6G) markers. Osteoclast number was determined by TRAP and gene expression of RANKL, MMP-13, TNF-a, IL-6 and IL-10 in the gingival tissues was evaluated by RT-qPCR. In the first publication, μCT analysis showed a significantly greater inflammatory bone resorption in Ipaf-KO mice; however there was no difference between WT and Ipaf-KO on osteoclast numbers of inflammatory infiltrate. Expression of candidate genes was also similarly increased by the induction of experimental periodontal disease, except for the expression of TNF-alpha and IL-10, which was already significantly higher in the gingival tissues of Ipaf-KO mice in the absence of experimental periodontal disease. We conclude that NLRC4 inflammasome has a protective role on inflammatory bone resorption in this experimental model. In the second publication we observed that severity of bone resorption was not affected by the lack of NLRP3 inflammasome, but it was reduced in Casp1-KO mice. Interestingly, the attenuation of alveolar bone resorption in Casp1-KO mice was accompanied by increase on the number of osteoclasts, whereas there were no significant changes on the inflammatory infiltrate or expression of candidate genes. The conclusion was that NLPR3 inflammasome does not play a significant role in induced inflammation and bone resorption and caspase-1 has a pro-resorptive role in these conditions.